Розробка програмного додатку до аналітичного застосунку - Моісеєнко, Д. В. (ХНУРЕ, 2025)
This paper considers the methodology for developing an analytical web application that combines the efficiency of data processing with the convenience of an interactive user interface. The proposed approach involves the use of a modern technological stack to create a scalable and secure system [1]. Particular attention is paid to automated communication with data sources, effective management of user sessions, and integration of mechanisms for fast querying and real-time information visualization. The possibilities of optimizing query processing speed by using Drizzle ORM as a tool for database manipulation [2] are investigated. The results obtained demonstrate the advantages of the proposed architecture for use in business analytics and scientific research.
Keywords: аналітичний застосунок; програмний додаток